1997
DOI: 10.1076/ceyr.16.1.26.5116
|View full text |Cite
|
Sign up to set email alerts
|

Experimental preretinal neovascularization by laser-induced venous thrombosis in rats

Abstract: This is a new model of retinal ischemia and associated neovascularization established by venous thrombosis that is easily reproducible. Many aspects of rat retinal physiology are known and this model has promise as an avenue for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…These results indicate that FITC-dextran angiography is a good method of quantifying preretinal neovascularization of the entire retina. Saito et al (1997) reported a 70% (19/27) rate of preretinal neovascularization production in pigmented adult rats using photodynamic venous occlusion with systemic fluorescein dye injections examined by FAG. Kang et al (1999) reported a 90% (9/10) rate of preretinal neovascularization production in albino adult rats using photodynamic venous occlusion with systemic rose bengal dye injections examined by ADPase staining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate that FITC-dextran angiography is a good method of quantifying preretinal neovascularization of the entire retina. Saito et al (1997) reported a 70% (19/27) rate of preretinal neovascularization production in pigmented adult rats using photodynamic venous occlusion with systemic fluorescein dye injections examined by FAG. Kang et al (1999) reported a 90% (9/10) rate of preretinal neovascularization production in albino adult rats using photodynamic venous occlusion with systemic rose bengal dye injections examined by ADPase staining.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, preretinal neovascularization is definitely present 14 days after venous occlusion (Saito et al 1997;Kang et al 1999). Therefore, animals were killed accordingly in this experiment.…”
Section: Image Observation and Analysis Of Preretinal Neovascularizatmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one days after viral injections, PNV was induced by laser-induced retinal vein occlusion according to an established method with modifications [23,24]. Rose bengal sodium salt (certified purity 90%; Sigma, St. Louis, Mo., USA) was prepared at a concentration of 50 mg/ml with an isotonic sodium chloride solution.…”
Section: Induction Of Pnv By Laser-induced Retinal Vein Occlusionmentioning
confidence: 99%